FAKTOR-FAKTOR YANG BERHUBUNGAN TERHADAP PELAKSANAAN IMUNISASI MEASLES RUBELLA - Sayati, Dewi - (Masker Medika, 2020)
Abstract Background: Measleas Rubella immunization is a combination immunization to prevent measles, mumps, German measles (rubella), and diseases given by the RNA virus from the Togavirus class. Rubella is a viral disease that occurs in children and young adults. Symptoms include fever, cough, conjunctivitis and skin rash. According to data, the coverage of Posyandu Cempaka and Kenanga is 73.25%, with the lowest 9 out of 41 health centers in Palembang.Methods: The research design used was an analytic survey with a cross sectional approach and a sampling technique using a total sampling of 63 respondents, which was then performed a chi-square statistical test, with a confidence degree of 95%.Results: the results of statistical tests showed that there was a relationship between knowledge (p value 0.003), attitude (p value 0.002), family support (p value 0.001), the role of officers (p value 0.007) with the implementation of Measleas Rubella immunization, and there was no relationship between distance exposure (p value 0.092), and the role of community leaders (p value 0.101) with the implementation of Measleas Rubella immunization.